2009
DOI: 10.1007/s12576-009-0046-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexamethasone on the expression of β1-, β2- and β3-adrenoceptor mRNAs in skeletal and left ventricle muscles in rats

Abstract: Glucocorticoids are known to increase the density and mRNA levels of beta-adrenoceptors (beta-AR) via the glucocorticoid receptor (GR) in many tissues. However, the effects of these changes in the skeletal and cardiac muscles remain relatively unknown. We have investigated the effects of dexamethasone on the expression of the beta(1)-, beta(2)-, and beta(3)-AR mRNAs and GR mRNA in fast-twitch fiber-rich extensor digitorum longus (EDL), slow-twitch fiber-rich soleus (SOL), and left ventricle (LV) muscles by rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 36 publications
4
31
0
Order By: Relevance
“…Experiments were designed to minimize pain and discomfort for the rats. [19][20][21] Both experiments were approved by the Committee on Animal Care Use at Waseda University. Administration of Dexamethasone to Rats --Dexamethasone 21-phosphate (Sigma, St. Louis, MO, U.S.A.) was first dissolved in 0.9% NaCl solution as a vehicle to obtain a final dexamethasone concentration of 0.1%.…”
Section: Fig 1 Experimental Protocol Used In the Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments were designed to minimize pain and discomfort for the rats. [19][20][21] Both experiments were approved by the Committee on Animal Care Use at Waseda University. Administration of Dexamethasone to Rats --Dexamethasone 21-phosphate (Sigma, St. Louis, MO, U.S.A.) was first dissolved in 0.9% NaCl solution as a vehicle to obtain a final dexamethasone concentration of 0.1%.…”
Section: Fig 1 Experimental Protocol Used In the Present Studymentioning
confidence: 99%
“…Administration of Dexamethasone to Rats --Dexamethasone 21-phosphate (Sigma, St. Louis, MO, U.S.A.) was first dissolved in 0.9% NaCl solution as a vehicle to obtain a final dexamethasone concentration of 0.1%. 21) In the dexamethasonetreated group, dexamethasone was administered at the cervical region of the back via a subcutaneous injection (s.c., 9:00-9:30 a.m.). 21) In the control group, an equivalent volume of dexamethasone-free solution was administered in the same manner.…”
Section: Fig 1 Experimental Protocol Used In the Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…17) Animal chow (CL-2, CLEA Japan Inc.) and onceboiled tap water were given to the rats ad libitum. 18) After the adaptation periods, the rats were randomly divided into the AITC group and the control group (1st experiment), and, the rats were randomly divided into the AITC group (10 mg/kg body weight per day), AITC group (20 mg/kg body weight per day) and the control group (2nd experiment).…”
Section: Methodsmentioning
confidence: 99%
“…Glucocorticoids also increased the expression and activity of the ubiquitin-proteasome pathway that play an important role in the major proteolytic mechanism of muscle atrophy (Bodine et al, 2001;Hasselgren, 1999). Some reports showed that the degree of synthesized glucocorticoid, dexamethasone Synthesized glucocorticoid, dexamethasone regulates the expressions of β 2 -adrenoceptor and glucocorticoid receptor mRNAs but not proteins in slow-twitch soleus muscle of rats (DEX)-induced decrease in muscle weight was higher in fast-twitch fiber-rich (extensor digitorum longus (EDL)) muscle than in slow-twitch fiber-rich (soleus (SOL)) muscle (Kawano et al, 2009;Livingstone et al, 1981).…”
Section: Introductionmentioning
confidence: 99%